The Effect of Employer Branding on Contractual Employees: Engagement and Discretionary Effort - Hardy, Human; Afrianty, Tri Wulida; Prasetya, Arik (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
Employees are the most valuable assets in various types of organizations, and to retain valuable employees, organizations need employer branding strategies. This study examines the effect of employee engagement as a mediator variable of employer branding and discretionary effort relations. The sample used in this study are 110 contractual employees who worked at the State-Owned Enterprises (SOE) Commercial Banks in Kota Malang. The data in this study were collected through direct surveys using questionnaires. Explanatory methods and Structural Equation Modeling (SEM) are used to explain the influence between variables. The results of this study indicate that employer branding has a positive and significant effect on employee engagement of contractual employees and positive but not significant effect on discretionary effort of contractual employees. This study also proves the role of employee engagement that successfully mediates the influence of employer branding on discretionary effort to be positive and significant. The role of employee engagement becomes essential, indicating SOE Commercial Banks should increase contractual employee’s engagement level before expecting an enhancement on discretionary effort through employer branding strategy.